T. S. Eliot in context - Harding, Jason (Cambridge University Press, 2011)
"T. S. Eliot's work demands much from his readers. The more the reader knows about his allusions and range of cultural reference, the more rewarding his poems, essays and plays are. This book is carefully designed to provide an authoritative and coherent examination of those contexts essential to the fullest understanding of his challenging and controversial body of work. It explores a broad range of subjects relating to Eliot's life and career; key literary, intellectual, social and historical contexts; as well as the critical reception of his oeuvre. Taken together, these chapters sharpen critical appreciation of Eliot's writings and present a comprehensive, composite portrait of one of the twentieth century's pre-eminent men of letters. Drawing on original research, T. S. Eliot in Context is a timely contribution to an exciting reassessment of Eliot's life and works, and will provide a valuable resource for scholars, teachers, students and general readers"--